The Link Between Economic Growth and Poverty in Indonesia - Wardana, Vidia (Outline Journal of Economic Studies, 2023)
Indonesia is the third largest rice producer in the world and number one in Southeast Asia with an estimated production of 34.6 million tons MT. Indonesia is a country that consumes a lot of rice. Continuous requests from almost everyone in Indonesia. The purpose of this article is to describe the factors that affect the demand for and supply of rice in Indonesia. The type of research in this research is associative research and descriptive analysis. Public demand and supply of rice products by entrepreneurs in Indonesia experience different changes, and the relationship between the two is not necessarily balanced. The Indonesian government needs to evaluate the mechanism of rice planting, harvesting, distribution and marketing in Indonesia and food companies that handle the distribution and marketing of rice commodities throughout Indonesia and maximize sales of rice collection and processing to the Indonesian people. The supply and demand for rice in Indonesia are influenced by several factors such as export and import operations, structural issues, the business environment and issues related to demand and supply.